Antidotal or protective eﬀects of honey and one of its major polyphenols, chrysin, against natural and chemical toxicities - Samarghandian, Saeed; Azimi-Nezhad, Mohsen; Pourbagher Shahri, Ali Mohammad; Farkhondeh, Tahereh (Acta Biomedica Atenei Parmensis, 2019)
Objective: Honey and its polyphenolic compounds are of main natural antioxidants that have been used in traditional medicine. The aim of this review was to identify the protective effects of honey and chrysin (a polyphenol available in honey) against the chemical and natural toxic agents. Method: The scientific databases such as MEDLINE, PubMed, Scopus, Web of Science and Google Scholar were searched to identify studies on the antidotal effects of honey and chrysin against toxic agents. Results: This study found that honey had protective activity against toxic agents-induced organ damages by modulating oxidative stress, inflammation, and apoptosis pathways. However, clinical trial studies are needed to confirm the efficacy of honey and chrysin as antidote agents in human intoxication. Conclusion: Honey and chrysin may be effective against toxic agents. (www.actabiomedica.it)